Konsep Penataan Tanaman pada Perkampungan Budaya Betawi Setu Babakan, Jagakarsa, Jakarta Selatan - Ardana Reswari; Qurrotu Aini Besila; Eko Adhy Setiawan (Jurnal Lingkungan dan Kota, 2021)
To keep and maintain the values of Betawi community cultural arts and environment, the Regional Government of the Special Capital Region of Jakarta felt the need to realize the Betawi Cultural Village, namely through the Governor’s Decree Special Capital Region of Jakarta No. 92 of 2000, concerning Environmental Arrangement of Betawi Cultural Village in Srengseng Sawah Village, Jagakarsa District, South Jakarta Municipality. Several types of tourism potential developed in the Betawi Cultural Village covering an area of approximately 165 hectares are cultural tourism, agro tourism and water tourism, given the presence of Setu Babakan and also Setu Mangga Bolong in the area. Agro tourism itself is a form of tourism activity that utilizes agriculture (agro) as a tourist attraction. The attraction and uniqueness of agro tourism in the Betawi Cultural Village, the plantation location is not in a special area, but is in the yard of the Betawi Cultural Village Setu Babakan and in the yards of residents' houses. To prioritize Betawi nuances in yards and various other green open spaces, it is necessary to arrange plants that are capable of depicting the faces of the yards, gardens and green open spaces of the Betawi people in the past. It is necessary to investigate the types of plants commonly used by the Betawi people in the past, as well as their composition and cropping patterns, as well as data collection on the latest conditions in the Betawi Cultural Village. The comparison between the two will be the basis of reference for establishing the concept of planting as an effort to preserve culture and plants so that their existence can still be enjoyed by the current community and in the future.